PEMBELAJARAN SENI BACA AL-QUR'AN DI PESANTREN AL MUSTAQIMIYAH BOGOR - Susanti, Yanti; Jazila, Selma Tahlis (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2025)
The art of reciting the Qur'an is a form of recitation that pays special attention to tajwid, which is a set of rules and principles that govern the correct pronunciation of the letters of the Qur'an. At the Al Mustaqimiyah Islamic Boarding School in Bogor, teaching this art is an initiative that aims to improve the students' recitation skills and quality, with a special emphasis on the use of the Nahawand tone. However, the implementation of this program is not without obstacles. These challenges include a shortage of teachers skilled in the art of reciting the Qur'an, inadequate learning facilities, and low motivation among students to participate. This community service activity aims to provide solutions to these challenges by strengthening students' understanding and skills in reciting the Qur'an through an interactive, innovative, and practical teaching approach. To achieve this, a systematic problem-solving framework is needed. The methods applied must introduce the basic principles of rhythm and tone, include quizzes on reciting the Qur'an using certain melodies, establish a structured curriculum, and include regular evaluations. The results of the analysis show that this program has succeeded in improving the students' Quran reading skills. With innovative teaching methods, it is hoped that the overall quality of learning will continue to improve, so that students will not only become proficient readers but also individuals who understand the meaning contained in the Quran. Based on the Community Service (PKM) activities carried out at the Al Mustaqimiyah Islamic Boarding School, it can be concluded that the art of learning to read the Qur'an not only involves technical mastery of reading but also requires a deep understanding of the meaning and context of the verses of the Qur'an. The PKM program implements various strategies, ranging from direct teaching by experienced teachers to the integration of modern tools such as Quran learning applications.ABSTRAKSeni tilawah Al-Qur'an adalah bentuk pembacaan yang memberikan perhatian khusus pada tajwid, yaitu kumpulan aturan dan prinsip yang mengatur pengucapan huruf-huruf Al-Qur'an dengan benar. Di Pesantren Al Mustaqimiyah Bogor, pengajaran seni ini merupakan inisiatif yang bertujuan untuk meningkatkan kemampuan dan kualitas tilawah santri, dengan penekanan khusus pada penggunaan nada Nahawand. Namun, pelaksanaan program ini tidak tanpa hambatan. Tantangan tersebut meliputi kekurangan guru yang mahir dalam seni pembacaan Al-Qur'an, fasilitas belajar yang tidak memadai, dan motivasi santri yang rendah untuk berpartisipasi. Kegiatan pengabdian masyarakat ini bertujuan untuk memberikan solusi atas tantangan tersebut dengan memperkuat pemahaman dan keterampilan santri dalam pembacaan Al-Qur'an melalui pendekatan pengajaran yang interaktif, inovatif, dan praktis. Untuk mencapai hal ini, diperlukan kerangka kerja pemecahan masalah yang sistematis. Metode yang diterapkan harus memperkenalkan prinsip dasar ritme dan nada, menyertakan kuis pembacaan Al-Qur'an menggunakan melodi tertentu, menetapkan kurikulum yang terstruktur, dan termasuk evaluasi rutin. Hasil analisis menunjukkan bahwa program ini berhasil meningkatkan keterampilan pembacaan Al-Qur'an santri. Dengan metode pengajaran inovatif, diharapkan kualitas pembelajaran secara keseluruhan akan terus berkembang, sehingga santri tidak hanya menjadi pembaca yang mahir tetapi juga individu yang memahami makna yang terkandung dalam Al-Qur'an. Berdasarkan kegiatan Pengabdian kepada Masyarakat (PKM) yang dilaksanakan di Pesantren Al Mustaqimiyah, dapat disimpulkan bahwa seni pembelajaran pembacaan Al-Qur’an tidak hanya melibatkan penguasaan teknis membaca, tetapi juga memerlukan pemahaman mendalam terhadap makna dan konteks ayat-ayat Al-Qur’an. Program PKM menerapkan berbagai strategi, mulai dari pengajaran langsung oleh guru berpengalaman hingga integrasi alat modern seperti aplikasi pembelajaran Al-Qur’an.